PENGARUH LITERASI DAN INKLUSI KEUANGAN TERHADAP PENGGUNAAN FINTECH GOPAY PADA KARYAWAN WANITA SWASTA DI KOTA JAKARTA - Darkiman Ruminta; Dwi Oktaviani (Politeknik Bisnis Indonesia, 2024)
The Indonesian government will continue to encourage financial literacy and financial inclusion to achieve the Financial Inclusion Index goal of 90 percent by 2024. Therefore, the role of financial services needs to be optimized to expand access for people who still lack financial literacy. In the future, women will be the economic drivers who dominate spending in the world. This is because women have many important roles in their lives, starting with their role in the family as mothers to their role in society as woman entrepreneurs. The aim of the research is to determine: (1) The influence of financial literacy on the use of financial technology (GoPay). (2) The influence of financial inclusion on the use of financial technology (GoPay). (3) The influence of financial literacy and financial inclusion on the use of financial technology (GoPay). This research uses quantitative methods with a sample of 100 female private employees in the DKI Jakarta area who have used or have used GoPay as a payment system. Calculation, processing and presentation of data using statistical tests assisted by using the Jeffrey's Amazing Statistics Program (JASP). Based on the research results, it is known that financial literacy and financial inclusion have a positive influence on the use of GoPay financial technology among female private employees in the city of Jakarta. This is also supported by the results of the determinant coefficient test (r2) where it is known that financial technology can be explained by financial literacy and financial inclusion by 61.4% while the other 38.6% is explained by variables outside the research. Even though the percentage level of financial technology variance is quite high, researchers hope that in future research they can use other variables not mentioned in the research, and use more samples to get results that are more representative of the population size.